Perlindungan Warga Negara Terhadap Perbuatan Melawan Hukum Pemerintah Melalui Penyelesaian Sengketa Di Peradilan Tata Usaha Negara - Delfina Gusman; Anton Rosari; Arya Putra Rizal Pratama (Faculty of Law, Universitas Riau, 2021)
State administration dispute, one base from the state administration decision, that law subject prejudice have cause big harmful with society if dispute resolution very long and unefficient. This is also ruin as good will of law justice in middle of public as for social image. This is about good topic to discuss by law practicion, law academic or expert and society as for sovereignty dominate, that the cause a people are got court decision in kracht but always wit social-economy charge after asking about State Administration Court implementation a court decision. Last result of of the research by law theorical it can be recommendation to goverment to change regulation that affection with compensation punishment after state administration law desicion to give with law subject and also find other solution for settle a dispute in non-litigation with goverment princple of law or good govermental. And also law practition to overcome to reinforcement in court.This research with docrinal research by library research and statue approach. The craracteristic of law research a prescription that a analysing law statue and law material by electronic or book and tell about solution against this law problem.